Awareness of age-related gains and losses in a national sample of adults aged 80 years and older: cross-sectional associations with health correlates - Kaspar, Roman; Wahl, Hans-Werner; Diehl, Manfred (Innovation in Aging, 2023)
Advanced old age is a life stage with a high likelihood of age-related loss experiences. However, little is known about remaining gain experiences and their relation with perceived losses and health correlates in community-dwelling very old adults. Moreover, virtually nothing is known in this regard about the experiences of individuals in long-term care settings. First, we strived to establish the normative course of age-related gains and losses in advanced old age. Second, we examined whether such gain/loss perceptions in advanced aging moderated health correlates.Data came from the nationally representative survey “Old Age in Germany D80+” conducted in 2020/2021. The sample comprised 10 578 individuals aged 80-106 years, including 587 individuals in long-term care. We used the multidimensional Awareness of Age-Related Change (AARC) questionnaire and moderated regression to analyze associations with late-life health and functioning correlates.Levels of AARC-Gains were higher than those of AARC-Losses across most of the age range. Long-term care residents showed more AARC-Losses and fewer AARC-Gains compared with community-dwelling adults and contributed significantly to an overall negative balance of more losses than gains in those aged 90 years or older. Regarding functional health and autonomy, negative age effects were amplified by AARC-Losses, but buffered by AARC-Gains. A more positive ratio of gains-to-losses predicted better health and functioning.Findings suggest that the loss aspect of development in very late life might have been overstated in the existing literature. Perceived gains and losses are of critical importance for the understanding of health correlates in very old age.